Passando a boiada: retrocessos no estado de direito agroambiental por atos do governo federal no mandato presidencial de Jair Bolsonaro - CASTRO, Géssica Cristiane Souza de (2022)
This work aims to explore the setbacks in the Agri-environmental Rule of Law during the first two years of President Jair Bolsonaro's presidential term. This is an issue of great importance, especially because of the need to consolidate the means of agri-environmental protection. Through the inductive method, the advancement of the concept of State models was examined until we get to the current proposal of a State of Law model that takes into consideration the agrarian and environmental dimension, from the perspective of respect for human dignity. We also examined the current protection structures that are part of the Agri-environmental Rule of Law, consolidated after decades of normative construction and culminating with the advent of the 1988 Federal Constitution. Finally, the Federal Government's non-legal normative acts in agri-environmental matters were examined, inside the limit of the time interval demarcated for this study, which present potential damage and a high risk of setback. It was concluded that, in order to provide greater flexibility to the means of agri-environmental protection, the federal government has used insidious changes in the legal means of protection through non-legal normative acts, modifying normative interpretations and regulations, modifying the structure of executive bodies, consultative and deliberative.